A review on castor oil - M. H., Ahmad; J., Sazali; Izirwan, Izhab; W. A., Ibrahim; Zulkafli, Hassan (2018)
Castor oil is an oil derived from castor seed from a plant Ricinus Communis. It is an inedible oil which could be dangerous to humans if consumed like sickness. However, castor oil actually can be used to produce many valuable products such as chemicals, paint, cosmetic due to its unique characteristic which contains high percentage of ricinoleic acid that really helps in producing many valuable products. The utilization of vegetable oils is currently in the highlight of the chemical industry, as they are one of the most important renewable resources due to their universal availability, inherent biodegradability, low price, and eco-friendly. Therefore, the main aim of this paper is to focus on the background, characteristic, composition, properties and industrial application of castor oil. Hopefully, it could catch researchers’ attention that toxic seed which contains ricin that could possibly kill at first actually has much greater potential than others available vegetable oils to in this world. The versatility of castor oil is highly attributed by 12-hydroxy-9-octadecenoic acid (ricinoleic acid) and its functional group.